2020
DOI: 10.1002/chem.202002511
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conjugated π‐Systems Arising from Cannibalistic Hexadehydro‐Diels–Alder Couplings: Cleavage of C−C Single and Triple Bonds

Abstract: We have investigated the cannibalistic self-trapping reaction of an ortho-benzyne derivativeg eneratedf rom 1,11-bis(p-tolyl)undeca-1,3,8,10-tetrayne in an HDDA reaction. Without adding anys pecific trapping agent, the highly reactiveb enzyne is trapped by anotherb isdiyne molecule in at least three different modes.W eh ave isolated and characterized the resulting products and performed high-level calculations concerning the reactionm echanism. During the cannibalistic self-trapping process, either aC Ct riple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…S6 †). The "open" conformation was shown to be the structure of groundstate Me-BD-Me in the solid state by single-crystal X-ray diffraction, 94 and our DFT calculations on Me-BD-Me also indicate a preference for the open conformation with DG(Open) À DG(Closed) ¼ À3.3 kJ mol À1 in favor of the open conformer. However, it is logical to assume that the "closed" conformation leads to an increased HDDA reaction probability between the two -C^C-C^Cunits in the excited state because the two units have to approach each other for the reaction to occur.…”
Section: Transient Absorption Experimentsmentioning
confidence: 57%
See 4 more Smart Citations
“…S6 †). The "open" conformation was shown to be the structure of groundstate Me-BD-Me in the solid state by single-crystal X-ray diffraction, 94 and our DFT calculations on Me-BD-Me also indicate a preference for the open conformation with DG(Open) À DG(Closed) ¼ À3.3 kJ mol À1 in favor of the open conformer. However, it is logical to assume that the "closed" conformation leads to an increased HDDA reaction probability between the two -C^C-C^Cunits in the excited state because the two units have to approach each other for the reaction to occur.…”
Section: Transient Absorption Experimentsmentioning
confidence: 57%
“…1, path 3 gray) were also isolated and identied. 94 Although the isolated products arose from a thermal reaction, it has been reported that the HDDA products arising from both the thermally and photochemically generated o-benzyne intermediate are the same. 83 Thus, it was assumed that the electronic state of the o-benzyne intermediate is the same in both cases.…”
Section: Double-hydrogen Transfermentioning
confidence: 99%
See 3 more Smart Citations